Regulations Governing the Transfer and Transplantation of Human Organs: A Comparative Study - Mousa, Salma Ali; Doub, Aisha A. (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
The process of organ transplantation is a contemporary medical issue that doctors have recently resorted to as a means of treatment, and it has become necessary in some critical and urgent cases. Due to its wide spread in the medical field and its remarkable successes, it has become one of the real-world issues that Muslims must follow to understand the Sharia's perspective on its legitimacy and its compliance with its rules and regulations. This has led Sharia scholars to examine it through the lens of Islamic law and explore its alignment with the objectives of Sharia. The research aimed to clarify the views of Islamic law on this procedure, the regulations accompanying it, and compare all of this with the legal texts in Libyan legislation, while referencing some contemporary legislation from other countries. The research addresses the study of organ transplantation from its inception, how it originated, and how it has become a means of treatment. It also explores the forms of transplantation, clarifying which forms are prohibited and which are permissible, the essential elements required for the completion of the procedure, and the regulations governing it to make it permissible and beneficial. Additionally, it compares these regulations between Sharia and Libyan criminal law. The research includes an introduction, a preface, two chapters, a conclusion, and an index. The introduction covers the objectives and importance of the research, the reason for choosing the topic, the research problem, the research hypothesis, and methodology. The first chapter addresses organ transplantation from a living donor to another living person, divided into two sections: the first section discusses the Sharia ruling on transplantation, and the second section discusses the Sharia and legal regulations for transplantation. The second chapter discusses organ transplantation from a deceased donor to a living person, also divided into two sections: the first section covers the Sharia ruling, and the second section covers the regulations in both Sharia and law. The conclusion highlights the agreement between Sharia and the law on the permissibility of donation and the prohibition of organ sales, as well as the limited attention of the Libyan legislator to enacting many laws regulating transplantation and combating organ trafficking, along with a set of recommendations.
Keywords: Transplantation; Organs; Transfer; Death; Alive; Regulations